Pengenalan Media Pembelajaran Berbasis Video Animasi untuk Meningkatkan Motivasi belajar Siswa di SDN 110 Lura - Taba Pasampuri; Syarifnur; Jusman (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
Education plays a very important role in measuring the progress of a nation because education is a process experienced by humans to study their environment in order to become a complete human being. With education, a person can develop the potential within himself to become a person with personality. Education can be provided in two ways: formal and non-formal. This research was conducted using a descriptive qualitative method to describe the phenomenon of the effectiveness of animated video learning media in elementary schools. This methodology involves direct observation at the research site, namely at SDN 11O Lura, to monitor students’ behavior and response to the animated video learning media. In addition, interviews with teachers and students were conducted to obtain further information on how the animated video learning media affects students’ learning motivation and academic outcomes. Interpretation of the results of this study is described in detail to provide a clear picture of how the animated video learning media is effective in improving learning motivation and learning outcomes of primary school students.Learning is the effort of an educator to achieve a goal and improve learning. It is an activity in which a person acquires knowledge, skills, and values by using various sources. Learning through information and communication technology depends on the role of the educator as a facilitator, not the source. In addition, it can be used as a learning medium or help intermediaries achieve learning objectives. The use of animated videos can increase students’ interest in learning in elementary school. Learning is a process that involves the role of the educator as a facilitator in helping students acquire knowledge, skills and values. This media offers various advantages such as displaying a combination of text, color images, audio, and animation that can increase students’ interest and understanding of learning materials. The creation of learning animation videos has two approaches: self-creation by subject teachers and utilization of videos available on platforms such as YouTube. For relatively simple materials such as Pancasila education, teachers can make their own animated videos. While for more complex materials, teachers can utilize learning videos from YouTube that are tailored to the learning topic